PEMBERDAYAAN UMKM ECOENZIM BERBASIS KEARIFAN LOKAL DI DESA RAMA AGUNG ARGAMAKMUR BENGKULU UTARA - Syafri, Fatrica; Yani, Neni Putri; Pami Aprilina, Rahmadia; Agustina, Rahma Ayu; Sari, Suci Amanda (CV. Kalimasada Group, 2024)
This community service program aims to empower MSMEs in Rama Agung Village, Argamakmur, North Bengkulu, through the development of eco-enzyme products based on local wisdom. The methods used in this program are Asset-Based Community Development (ABCD) and Participatory Action Research (PAR), which actively involve the community in the production and marketing processes. This program successfully converted fruit peel waste into eco-enzyme soap, which is not only environmentally friendly but also increased the income of the assisted groups. The results of the mentoring show success in enhancing production capacity and market expansion to areas outside the city. The conclusion of this program is that MSME empowerment based on local wisdom can be an effective solution for improving economic welfare and environmental sustainability.